L’essor du nationalisme civique au pays de Galles(années 1960-années 1990) : quelques réflexions - Didier Revest (Revue Française de Civilisation Britannique, 2006)
It is often taken for granted that, in Wales, over the last fifty years or so, ethnic nationalism, which is culture-based, has given way to a more open, democratic form of nationalism, ie. the so-called ‘civic ideal’ in which equal citizenship is given pride of place, whatever one’s social, cultural or religious background. The purpose of the paper is to show that the dichotomy is far from valid; indeed, civic (or institutional) nationalism is arguably just another way, though a more elaborate one, of celebrating ethnicity, which ultimately raises the question of its limits in a diverse society like Wales.